2014
DOI: 10.1136/neurintsurg-2014-011466
|View full text |Cite
|
Sign up to set email alerts
|

Assisted coiling of saccular wide-necked unruptured intracranial aneurysms: stent versus balloon

Abstract: Stent-assisted coiling achieved better results in terms of complete occlusion and stability than balloon-assisted coiling with a lower rate of recurrence without being associated with a higher risk of intraprocedural complications. Bifurcational and large to giant aneurysms were associated with higher complication rates and higher recurrence rates, respectively, and still represent a challenge for both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 16 publications
(10 reference statements)
2
38
0
Order By: Relevance
“…Some studies have even reported that in some AcoA aneurysm embolization procedures, the surgical procedure has been changed to surgical clipping due to finding a small aneurysm diameter or an inappropriate aspect ratio (dome/neck) ( 11 ). With the development of new balloons, stents, and more optimized catheter techniques, small or tiny AcoA aneurysms can also be successfully treated by interventional embolization; however, at present, it is not widely used, and long-term follow-up data are lacking ( 34 38 ). Some studies have investigated the relationship between the size of an AcoA aneurysm and the risk of intraoperative rupture, especially during interventional embolization.…”
Section: Relationship Between Aneurysm Size and Surgerymentioning
confidence: 99%
“…Some studies have even reported that in some AcoA aneurysm embolization procedures, the surgical procedure has been changed to surgical clipping due to finding a small aneurysm diameter or an inappropriate aspect ratio (dome/neck) ( 11 ). With the development of new balloons, stents, and more optimized catheter techniques, small or tiny AcoA aneurysms can also be successfully treated by interventional embolization; however, at present, it is not widely used, and long-term follow-up data are lacking ( 34 38 ). Some studies have investigated the relationship between the size of an AcoA aneurysm and the risk of intraoperative rupture, especially during interventional embolization.…”
Section: Relationship Between Aneurysm Size and Surgerymentioning
confidence: 99%
“…Although there was a 14% recurrence (3 major and 4 minor recurrences) on follow-up imaging (mean, 21 months), this recurrence rate is favorably comparable with the results reported in the literature. 4,15,20,21,[24][25][26] An intentional dog-ear remnant in coiling of a branch-incorporated aneurysm cannot be helped, though a dog-ear remnant may be a risk factor for recurrence. There was, however, no significant predictor of recurrence in this study.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,22,23 Notably, in our series, treatment-related morbidity occurred in only 1 patient (1.6%), which is acceptable in comparison with the reported results from the literature focusing only on wide necks and is also remarkable because adding an adjunctive device may lead to an increase in adverse events like thromboembolism and intraprocedural rupture. 24,25 Another concern is a possible increase in the recanalization rate after frequent incomplete coiling due to the complicated characteristics of the aneurysm. However, through the combination technique, only 1 incomplete coiling occurred in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Endovascular treatment of bifurcation IAs often requires stent placement with double stents in "Y" or "X" configurations, which could increase the risk of clinical complications, 7,8 whereas some authors reported low rates of complications compared with the balloon-remodeling technique. 9,10 Recently, 3 devices have been specifically developed for the endovascular treatment of such aneurysms arising at bifurcations: the WEB (Sequent Medical, Aliso Viejo, California), the pCONus (phenox, Bochum, Germany), and the PulseRider device (Pulsar Vascular, San Jose, California). The WEB is an intrasaccular braided-wire flow disruptor, 11,12 and the pCONus is a new stentlike self-expanding nitinol implant with 4 distal petals allowing coiling of the aneurysmal sac.…”
mentioning
confidence: 99%